2018
DOI: 10.1002/asia.201801336
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear Lanthanide Complexes Based on a Schiff‐base Ligand: Free Lattice Solvent Inducing the Single Molecule Magnet Behavior of Dy2 Compound

Abstract: Syntheses, crystal structures and magnetic properties are described for a series of seven‐coordinate dinuclear lanthanide complexes of compositions Dy2L2 (1) (H3L=2‐{[bis(2‐hydroxy‐3‐ethoxybenzyl)(aminoethyl)amino]methyl}phenol) and Ln2L2⋅MeCN (Ln=Dy (2), Sm (3), Eu (4), Gd (5), Tb (6), Ho (7)). The reaction of Dy(NO3)3⋅6 H2O with one equivalent of H3L at 70 °C in DMF/EtOH under autogenous pressure gave compound 1. Complexes 2–7 were prepared by means of the same method as that used for 1, except DMF was repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…Additionally, the Pc–Tb–Pc angle of TbPc 2 ·CH 2 Cl 2 is 179.715°, which is of the same magnitude as reported previously , and larger than that of TbPc 2 (179.104°). The chemical structure, including bond angles and bond lengths between the metal center and ligands, and the twist angle between ligands can influence the magnetic relaxation process of SMMs. ,,, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the Pc–Tb–Pc angle of TbPc 2 ·CH 2 Cl 2 is 179.715°, which is of the same magnitude as reported previously , and larger than that of TbPc 2 (179.104°). The chemical structure, including bond angles and bond lengths between the metal center and ligands, and the twist angle between ligands can influence the magnetic relaxation process of SMMs. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…The chemical structure, including bond angles and bond lengths between the metal center and ligands, and the twist angle between ligands can influence the magnetic relaxation process of SMMs. 18,23,50,51 To study the magnetic properties of TbPc 2 and TbPc 2 • CH 2 Cl 2 , the temperature dependence of molar magnetic susceptibility (χ M ) was measured in the temperature range of 2−300 K under a 1 kOe dc field. The χ M values of TbPc 2 and TbPc 2 •CH 2 Cl 2 are shown in Figure 3(a,b), respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several synthetic methodologies towards polynuclear cobalt clusters were established and one of the most efficient approaches involves the employment of hydroxy-containing Schiff base ligands. Schiff base ligands are easy to synthesize and their steric properties can be tuned by varying the size of the amine or carbonyl substituents (Qin et al, 2017(Qin et al, , 2018Ge et al, 2018;Li et al, 2021). More importantly, the hydroxy moieties of the Schiff base ligands can combine many metal ions with -O bridges, resulting in the formation of large polynuclear clusters.…”
Section: Introductionmentioning
confidence: 99%
“…For Dy 2 SMMs, there are two principal means of regulating their magnetic relaxation behavior. On one hand, the exchange coupling can be increased by using bridging radicals, heavier elements with more diffuse orbitals (such as Cl andS), aromatic cyclooctatetraenide (COT 2– ), and so on. On the other hand, the coordination environment of Dy III ions can be modulated by a subtle change in the crystal field, including varying the organic ligands in the original complexes, the lattice solvents, and the coordinated solvents. , In 2011, Murugesu et al reported a Dy 2 SMM, namely [Dy III 2 (L) 2 (NO 3 ) 2 ] ( Dy 2 -NO 3 , H 2 L = N 1, N 3-bis­(3-methoxysalicylidene)­diethylenetriamine), in which each Dy III ion coordinates one terminal nitrate anionic ligand . It was shown that the coordinated NO 3 – could be replaced by other bidentate, monoanionic ligands.…”
Section: Introductionmentioning
confidence: 99%